Algal polysaccharides: new perspectives for the treatment of basal ganglia neurodegenerative diseases - Lucena, Alessandra Marinho Miranda; de Souza Lucena, Eudes Euler; Neto, Sebastião Pacheco Duque; Nobre, Leonardo Thiago Duarte Barreto; Rocha, Hugo Alexandre Oliveira; Câmara, Rafael Barros Gomes (Frontiers in Neuroanatomy, 2024)
The objective of this review was to verify the therapeutic effect of polysaccharides derived from algae in neurodegenerative disease models involving the basal ganglia. To achieve this goal, a literature search was conducted in PubMed, Science Direct, Scopus, Web of Science, Embase, and Google Scholar databases. The descriptors “neuroprotective or neural regenerative or immunomodulatory activity or neuroprotection,” “polysaccharide or carbohydrate or carbohydrate polymers,” “marine algae or seaweed,” and “basal ganglia” according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) methodology were used. This methodology involved the steps of searching, pre-selection, and inclusion of articles. A total of 737 records were identified. Following the data analysis, 698 studies were excluded, resulting in a final sample of 8 studies. Species such as Turbinaria decurrens, Gracilaria cornea, Chlorella pyrenoidosa, Arthrospira (Spirulina) platensis, Fucus vesiculosus, and Laminaria japonica have demonstrated significant neuroprotective effects. This review suggests that polysaccharides derived from marine algae possess therapeutic potential for neuroprotection, modulation of inflammation, and amelioration of functional deficits. Their use in neurodegenerative disease models warrants further consideration.